2010
DOI: 10.1159/000285116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Muscarinic and Nicotinic Receptor Antagonism on Rat Gastric Motor Activity

Abstract: Background/Aims: Our aim was to investigate whether muscarinic and nicotinic receptors mediate nitric oxide release during motor events in the rat stomach. Methods: Isolated rat stomach volume changes were monitored in an organ bath setup with an intragastric balloon coupled to a barostat and studied in basal conditions and during electrical vagal stimulation (EVS). In conscious rats, the intragastric pressure (IGP) was measured during test meal infusion. Results: In the presence of NG-nitro-L-argin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We recently described a novel method to assess gastric accommodation in rats by measuring the IGP during nutrient infusion (26,27). Indeed, IGP is determined by the gastric muscle tone, and we demonstrated that increasing or decreasing the gastric tone during food infusion increased or decreased IGP, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…We recently described a novel method to assess gastric accommodation in rats by measuring the IGP during nutrient infusion (26,27). Indeed, IGP is determined by the gastric muscle tone, and we demonstrated that increasing or decreasing the gastric tone during food infusion increased or decreased IGP, respectively.…”
Section: Discussionmentioning
confidence: 85%